Conceptualization of frailty in rehabilitation interventions with adults: a scoping review. Issue 1 (2nd January 2023) - Kokorelias, Kristina M.; Cronin, Shawna M.; Munce, Sarah E. P.; Eftekhar, Parvin; McGilton, Katherine S.; Vellani, Shirin; Colella, Tracey J. F.; Kontos, Pia; Grigorovich, Alisa; Furlan, Andrea; Salbach, Nancy M.; Jaglal, Susan; et al.
Abstract: Purpose: We aimed to synthesize the literature that considered frailty in the evaluation of rehabilitation interventions for adults (aged ≥18) by answering: (1) how is frailty defined in rehabilitation intervention research?; (2) how is frailty operationalized in rehabilitation intervention research?; (3) what are the characteristics of rehabilitation interventions for frail adults and what frailty related outcomes are assessed? Materials and methods: A scoping review was conducted. Data were analyzed using descriptive statistics and qualitative content analysis. Results: 53 articles met the inclusion criteria. Most studies were conducted in Europe and involved randomized control trials. The included studies reported on rehabilitation interventions that only included individuals aged 50 or older. Thirteen studies used Fried's definition of frailty, but most ( n  = 27) did not use any definition. Many studies did not differentiate between the conceptualization (e.g., definition) and operationalization (e.g., use of inclusion/exclusion criteria, outcome measures) of frailty. Most interventions focused on exercise. Instrumental activities of daily living reported most frequently as outcomes ( n  = 11). Conclusions: There is an absence of consistent definitions of frailty in rehabilitation interventions and current definitions tend to focus on physical functioning. The authors suggest rehabilitation researchers consider an expanded definition of frailty informed by the International Classification of Functioning, Disability and Health framework. IMPLICATIONS FOR REHABILITATION: Rehabilitation professionals should use an expanded definition of frailty, informed by the International Classification of Functioning, Disability and Health framework, should include physical, mental, personal, environmental, and social factors to decrease, delay, or prevent frailty in adults. Rehabilitation professionals should consider a broader operationalization of frailty that is not dependent on age and physical functioning. Rehabilitation professionals that consider a broader conceptualization of frailty should tailor interventions to the specific needs of frail adults.